Pantun Dalam Kehidupan Melayu (Pendekatan historis dan antropologis) - Tuti Andriani (Sosial Budaya, 2012)
Poem is a poem in Malay literature of the most widely known. In the past rhymes are used to supplement the daily conversation. Even now the majority of Malays in the rural communities still use it. The word connotes a poem, like, like, for instance, or the like. For example, we often hear the words "Sepantun spiders, concocted in his own body". Sepantun word in the sentence above composition containing the same meaning as that disclosed in front of all. One characteristic that marks the poem is the first two lines are called sampiran or pembayang and two second array, called the content. Rhyme is used extensively by the Malays from all walks of life and on many occasions. Rhyme is very close to Malay life. Rhyme is considered as a form of art is born of instinct Malay culture itself. Even the last verse of usage life up to now in Malay. Even the rhymes are often made the song's lyrics, or even serve as the new expressions. Therefore, a guiding verse, the verse should serve to convey moral messages filled with the noble values of religious, cultural, and social norms of society. Through rhymes, those values are disseminated to the public, and bequeathed to his descendants.